Integrasi Strategi Pembelajaran Inkuiri dalam Pendidikan Agama Kristen untuk Mengembangkan Pemikiran Kritis Teologis Siswa (Sekolah Tinggi Agama Kristen Arastamar Grimenawa J, 2025)
Christian Religious Education (CRE) plays a strategic role in shaping students’ faith, character, and theological thinking. However, CRE learning is often delivered in a one-way manner, emphasizing doctrinal memorization, which hinders the development of contextual and critical faith reflection. This study aims to evaluate the implementation of the inquiry-based learning strategy in CRE and to assess its effectiveness in fostering students’ theological critical thinking. The central issue addressed in this research is the low level of student engagement in meaningful learning processes and their limited ability to connect faith teachings with real-life contexts. Employing a descriptive qualitative approach through in-depth analytical study, this research offers a novelty in the integration of inquiry strategies that enable students to ask questions, investigate, discuss, and reflect on faith teachings actively and contextually. The findings reveal that this strategy significantly enhances students’ understanding of biblical values, cultivates reflective theological responses, and strengthens the relevance of CRE to real-life situations. Inquiry-based learning proves to be a transformative and applicable pedagogical approach for contemporary CRE instruction.